People's Republic of China : Tax Policy and Employment Creation. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance report presents an international perspective on the employment impact of tax policy, and develops recommendations considering the background in the People's Republic of China. This report discusses the impact of tax policy including social security contributions on employment in China that covers both the taxation of employed labor and small- and medium-sized enterprises. The findings draw on economic theory, international experiences, as well as discussions with Chinese authorities during a workshop in Yangzhou and meetings in Beijing. The personal income tax on wages is low, but the tax wedge, which includes social security contributions, is high and follows an unsteady pattern, rising, falling, and again rising. The taxation of labor differs strongly by type and location of employment. The schedular system of the personal income tax means that labor taxes differ depending on the category into which income falls. Small businesses are offered some simplifications but are likely to still face disproportionally greater compliance costs.